An empirical evaluation of blockchain security models from a fuzzy statistical perspective. (28th June 2022) - Pampattiwar, Kalyani Nikhilesh; Chavan, Pallavi Vijay
Data must be conveyed in a way that only the intended entities can decode and comprehend it. Security is critical in the design of any data and process-intensive system. Researchers have developed a variety of protocols and security models to provide security – encryption models, hashing models, blockchain systems, secret sharing systems, etc. All these systems have their own nuances, advantages and limitations, making it challenging for system designers to choose the best security model. Delay-sensitive security systems, for example, should be able to secure data at high speeds with minimal complexity, however, this trait may jeopardise the system's security. In blockchain technology, secret sharing approaches improve the security performance of the systems. This review compares different blockchain and secret sharing techniques in terms of security, QoS performance, and computational complexity. These techniques pave the way for future security systems and can be combined for better QoS and security performance.